2015
DOI: 10.4067/s0718-95162015005000054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the phosphate solubilization potential of trichoderma strains (trichoplus jco) and effects on rice biomass

Abstract: This study aims to evaluate the phosphate solubilization potential of the Trichoderma spp. isolates found in the commercial product Trichoplus JCO. The strains were isolated, molecularly identified and grown in vitro. The soluble phosphate concentration was quantified at 3, 6, 9 and 12 days after transplanting. Rice was inoculated with the Trichoderma strains in greenhouse conditions with 10 to 60 x10 8 conidia per gram of rice and then planted. At 30 and 45 days after planting (DAP), plant growth characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Our results proved that both T. asperellum strains (Ta1 and Ta2) had a higher phosphate solubilization index (6 and 8 mm, respectively) as per a previous report [78] that T. asperellum Q1 was able to produce phosphatase enzymes for phosphate solubilization under salt stress conditions. Similar results were also recorded in another study [8], which found that T. asperelloides and T. harzianum were the highest phosphate solubilizers of five strains studied and suggested that Trichoderma strains used the solubilized phosphate in their cellular processes. These results were logical as it has been reported [79] that fungi have a large capability for solubilizing rock phosphate.…”
Section: Ability To Solubilize Insoluble Phosphatesupporting
confidence: 88%
See 2 more Smart Citations
“…Our results proved that both T. asperellum strains (Ta1 and Ta2) had a higher phosphate solubilization index (6 and 8 mm, respectively) as per a previous report [78] that T. asperellum Q1 was able to produce phosphatase enzymes for phosphate solubilization under salt stress conditions. Similar results were also recorded in another study [8], which found that T. asperelloides and T. harzianum were the highest phosphate solubilizers of five strains studied and suggested that Trichoderma strains used the solubilized phosphate in their cellular processes. These results were logical as it has been reported [79] that fungi have a large capability for solubilizing rock phosphate.…”
Section: Ability To Solubilize Insoluble Phosphatesupporting
confidence: 88%
“…The assay was modified from previously described method [8,56] to test the ability of Trichoderma strains for phosphate solubilization. Briefly, each strain was singly cultured on a Petri dish (100 mm) containing 10 mL of NBRIP agar composed of 10.0 g/L glucose,…”
Section: Ability To Solubilize Insoluble Phosphatementioning
confidence: 99%
See 1 more Smart Citation
“…According to Cornejo, Trichoderma enhances the lateral roots instead of the formation of new roots. Many authors have reported that during the process of P solubilization, the pH of the medium becomes acidified, probably due to the production of organic acids 30,[50][51][52] . Thus, a correlation between the decrease in pH and the increase in P solubilization influences the biomass increase of the lateral roots 12 and consequently increases the surface of P absorption by plants.…”
Section: Discussionmentioning
confidence: 99%
“…These results were supported by the past finding that RP maintained higher amount of AvlP in soil than SSP (Mandal and Khan, 1972). Again, the combined application of RP and PSB further increased soil AvlP compared to their individual application (Thakuria et al, 2009;Borges Chagas et al, 2015). Thus, it seems that PSB+RP and SRD in SSP Soil slurry+PSB+RP application could maintain a synchrony between the supply of soil AvlP and the rate of P uptake in plant over the crop growing period.…”
Section: Field Experiment-ii In Fertile Acid Soilmentioning
confidence: 90%